2021
DOI: 10.1111/1541-4337.12809
|View full text |Cite
|
Sign up to set email alerts
|

Pulse‐based snacks as functional foods: Processing challenges and biological potential

Abstract: Despite their high nutritional value and potential health benefits, pulse intake has not increased in the last three decades. Several strategies have been implemented to increase pulse consumption, such as their incorporation in bakery products, breakfast cereals, and snacks. The inclusion of pulses in these products could be an alternative to satisfy the consumers' demand for healthy foods. However, pulse-based snacks face important challenges, including reducing antinutritional factors, achieving consumer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 147 publications
(195 reference statements)
3
25
0
Order By: Relevance
“…Furthermore, data on the sensorial characteristics of these products provided indications to better identify target consumers as well as to develop bean-based products better adapted to consumer needs. From a nutritional standpoint, the use of composite flours containing common bean flour led, as expected and reported in similar studies [7,12,15,63,64], to products with higher protein and total dietary fiber content and lower amounts of starch and total carbohydrates. Depending on the type of pulse-based snacks (e.g., bars, biscuits, chips, bread, extruded snacks) reported protein concentration has ranged between 8.79% and 29.8%, with extruded snacks having the highest protein content, as they mostly or exclusively contain legume flour [7,64].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Furthermore, data on the sensorial characteristics of these products provided indications to better identify target consumers as well as to develop bean-based products better adapted to consumer needs. From a nutritional standpoint, the use of composite flours containing common bean flour led, as expected and reported in similar studies [7,12,15,63,64], to products with higher protein and total dietary fiber content and lower amounts of starch and total carbohydrates. Depending on the type of pulse-based snacks (e.g., bars, biscuits, chips, bread, extruded snacks) reported protein concentration has ranged between 8.79% and 29.8%, with extruded snacks having the highest protein content, as they mostly or exclusively contain legume flour [7,64].…”
Section: Discussionsupporting
confidence: 70%
“…From a nutritional standpoint, the use of composite flours containing common bean flour led, as expected and reported in similar studies [7,12,15,63,64], to products with higher protein and total dietary fiber content and lower amounts of starch and total carbohydrates. Depending on the type of pulse-based snacks (e.g., bars, biscuits, chips, bread, extruded snacks) reported protein concentration has ranged between 8.79% and 29.8%, with extruded snacks having the highest protein content, as they mostly or exclusively contain legume flour [7,64]. The direct comparison between the two types of biscuits produced in the current study with other bean-based biscuits previously described [12,15] showed that the protein content of Biscuit 1 and Biscuit 2 was higher (by on average 11%) than that (ranging between 8% and 10%) reported for biscuits containing bean flour ranging from 12% to 29%, indicating that the composition of the composite flour is also important if other flours beside common bean and wheat are used.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Then, the common bean baked snacks were individually packaged in resealable bags and stored at room temperature. In recent years, snack alternatives based on common beans have been developed to promote pulse consumption [8]. Meanwhile, consumers are changing their food preferences, choosing certain food products to obtain health benefits, and pulse-based snacks could satisfy this growing demand [9].…”
Section: Snack Preparationmentioning
confidence: 99%